Gastrodia longiflora (Orchidaceae: Epidendroideae: Gastrodieae), a new mycoheterotrophic species from Ishigaki Island, Ryukyu Islands, Japan - Suetsugu, Kenji (Phytotaxa, 2021)
Gastrodia Brown (1810: 330; Gastrodieae, Epidendroideae) is a mycoheterotrophic orchid genus distributed in temperate and tropical regions of Asia, Oceania, Madagascar, and Africa (Cribb et al. 2010, Hsu & Kuo 2010, Suetsugu et al. 2018). It is characterized by fleshy tubers, absence of normal leaves, united sepals and petals and two mealy pollinia without caudicles (Cribb et al. 2010, Hsu & Kuo 2010, Hsu et al. 2012, Suetsugu et al. 2018).